1997
DOI: 10.4269/ajtmh.1997.56.408
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Antigen by Monoclonal Antibodies for Immunodiagnosis of Angiostrongyliasis

Abstract: Two monoclonal antibodies, which recognize the epitope on an antigen with a molecular weight of 204 kD from the fifth-stage worm of Angiostrongylus cantonensis, were previously prepared and used to detect circulating antigens in patients with eosinophilic meningitis or meningoencephalitis and in mice experimentally infected with this parasite by a double-antibody, sandwich enzyme-linked immunosorbent assay (ELISA). The levels of this circulating antigen in experimentally infected mice were significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A sandwich ELISA using these mAbs for detection of circulating antigen in the serum of patients achieved high specificity (100%). However, the sensitivity, only 81%, was problematic (19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A sandwich ELISA using these mAbs for detection of circulating antigen in the serum of patients achieved high specificity (100%). However, the sensitivity, only 81%, was problematic (19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an immunoprecipitation analysis, a 204-kDa AcL 5 antigen could be detected by circulating antibodies in the serum of rats in early stages of experimental infestation (35 ). Indeed, two mAbs recognizing this antigen have been prepared previously (36 ) and have been applied for detection of circulating antigen in patients (19 ). A sandwich ELISA using these mAbs for detection of circulating antigen in the serum of patients achieved high specificity (100%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuamtanong [22] found that the reaction of serum antibodies to the 31-kDa antigen of A. cantonensis provided a more specific immunodiagnosis of angiostrongyliasis, and this was the technique used for confirming infection in our patient. The application of monoclonal antibody technology has recently been proposed for the detection of specific A. cantonensis antigens in serum and CSF specimens [23]. Further studies need to be done to confirm the suitability of this method in the identification of A. cantonensis infection.…”
Section: Discussionmentioning
confidence: 99%
“…In enzyme-linked fluorescent assays, the antibody detected the 91-kDa component in serum and CSF samples from infected patients with 88% sensitivity (Shih & Chen 1991). In the same way, Chye et al (1997) developed a monoclonal antibody that detects an antigen with a molecular weight of 204-kDa from L5 juveniles. This antibody showed greater sensitivity in CSF samples rather than serum samples.…”
mentioning
confidence: 99%